3D Laser Shock Peening – A new method for the 3D control of residual stresses in Selective Laser Melting. (15th September 2017) - Kalentics, Nikola; Boillat, Eric; Peyre, Patrice; Gorny, Cyril; Kenel, Christoph; Leinenbach, Christian; Jhabvala, Jamasp; Logé, Roland E.
Abstract: This paper describes a hybrid additive manufacturing process – 3D Laser Shock Peening (3D LSP), based on the integration of Laser Shock Peening (LSP) with selective laser melting (SLM). The well-known tensile residual stresses (TRS) in the as – built (AB) state of SLM parts in the subsurface region have a detrimental effect on their fatigue life. LSP is a relatively expensive surface post treatment method, known to generate deep CRS into the subsurface of the part, and used for high end applications (e.g. aerospace, nuclear) where fatigue life is crucial. The novel proposed 3D LSP process takes advantage of the possibility to repeatedly interrupt the part manufacturing, with cycles of a few SLM layers. This approach leads to higher and deeper CRS in the subsurface of the produced part, with expected improved fatigue properties. In this paper, 316L stainless steel samples were 3D LSP processed using a decoupled approach, i.e. by moving back and forth the baseplate from an SLM machine to an LSP station. A clear and significant increase in the magnitude and depth of CRS was observed, for all investigated process parameters, when compared to the AB SLM parts, or those traditionally LSP (surface) treated. Graphical abstract: Highlights: 3D LSP is a hybrid process which combines and applies Laser Shock Peening (LSP) during Selective Laser Melting (SLM) The LSP process converts the tensile residual stresses (TRS) to more beneficial compressive residual stresses (CRS) A smaller LSP spot size leads to a larger maximum CRS Higher LSP overlap rates lead to higher CRS and deeper CRS profiles The 3D LSP leads to higher and deeper CRS compared to conventional LSP, with expected improved fatigue properties